Kontribusi Penggunaan Model Discovery Learning terhadap Peningkatkan Kemampuan Koneksi dan Komunikasi Matematik pada Mahasiswa Program Studi Pendidikan Matematika Angkatan 2015-2016. - Haryani, Yeni (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
This study aims to determine the increase in the ability of connection and communication mathematics students better among the following study with the model of Discovery Learningdengan that follow the direct instruction, as well as to know the difference increased capacity connections and communication mathematics student groups of high, medium and low following study with the model Discovery Learning. The population in this study were all students of class 2015-2016. Samples were students of class D and E as an experimental class as the control class. The instrument used in this study includes test questions mathematical abilities and communication connections. Analysis of data using two different test average to better determine the increase between the experimental class and control class and one-way ANOVA with Scheffe test to determine the increase is better between groups of high, medium and low. Based on the research results, it can be concluded that the increase of connection and communication mathematical ability students who attend the learning model of Discovery Learninglebih better than students who attend hands-on learning. Improving the ability of connection and communication mathematics student groups are better than high and low groups that follow the model of learning with Discovery Learning.